Cardiovascular Risk and Factors Associated to the Health in Hypertensive African Descent People Resident in Quilombola Community - Rosa, Randson Souza; Ribeiro, Ícaro José do Santos; Silva, Jaine Kareny da; Souza, Luiz Humberto Rodrigues; Cruz, Diego Pires; Damasceno, Rudson Oliveira; Junior , Edison Vitório de Souza; Boery, Rita Narriman Silva de Oliveira (Revista Cuidarte, 2021)
Introduction: Hypertension is a cardiovascular risk factor of wide magnitude among people of African descent, especially those living in Quilombos.  However, little is known about the factors associated with cardiovascular risk in residents of the urban Quilombola community. Objetive: To analyze the cardiovascular risk and health-related factors in the family context of hypertensive Afro-descendants living in an urban Quilombola.  Materials and methods: It is a cross-sectional and community-based study carried out from November 2017 to March 2018. The study’s population consisted of 303 hypertensive patients enrolled in the family health unit, with ages ranging from 35 to 79 years old, of both genders; and using antihypertensive drugs. The instruments used for data production were: The Primary Arterial Hypertension Questionnaire and the Framingham Risk Score. Results: There was a significant association between cardiovascular risk and cardiovascular disease (CVD) family history (p
Keywords: Cardiovascular Disorders; Risk Factors; African Continental Ancestry Group; Vulnerability in Health